2015
DOI: 10.2147/ceg.s81929
|View full text |Cite
|
Sign up to set email alerts
|

Potentiated clinoptilolite reduces signs and symptoms associated with veisalgia

Abstract: IntroductionAbundant anecdotal evidence for products claiming to reduce veisalgia after alcohol overindulgence are available on the Internet and as many advertisements in journals. None of these claims are, however, substantiated by research. The aim of this research was to ascertain the validity of such claims for the substance Absorbatox™, a potentiated aluminosilicate (cation exchanger able to bind NH4+, histamine, and other positively charged ions) by investigating the signs and symptoms, as well as blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Moreover, a study in humans showed the ability of tribomechanically micronized clinoptilolite to decrease the absorption of ingested ethanol by reducing blood alcohol levels at a dose of 5 g ( Federico et al, 2015 ). If the clinoptilolite-containing product dosage is lower or if it is not administered at the time of alcohol consumption, this effect may not be visible as shown by Gandy et al (2015) where clinoptilolite still proved highly efficient in the reduction of veisalgia symptoms and signs up to 40–50%.…”
Section: Use Of Clinoptilolite In Veterinary and Human Medicinementioning
confidence: 99%
“…Moreover, a study in humans showed the ability of tribomechanically micronized clinoptilolite to decrease the absorption of ingested ethanol by reducing blood alcohol levels at a dose of 5 g ( Federico et al, 2015 ). If the clinoptilolite-containing product dosage is lower or if it is not administered at the time of alcohol consumption, this effect may not be visible as shown by Gandy et al (2015) where clinoptilolite still proved highly efficient in the reduction of veisalgia symptoms and signs up to 40–50%.…”
Section: Use Of Clinoptilolite In Veterinary and Human Medicinementioning
confidence: 99%
“…Important clinical trials have been conducted with respect to the reduction of episodes of heartburn by zeolite clinoptilolite as well as the decrease of mucosa erosion under consumption of non-steroidal anti-inflammatory drugs (Potgieter et al 2014). Symptoms of veisalgia caused by alcohol overindulgence can be significantly reduced by zeolite application without any effect on blood- or breath-alcohol level (Gandy et al 2015). It is important to note that all these symptoms within the stomach or of veisalgia are strongly connected with the endogenous histamine level, among others, which is implicated in the pathogenesis of gastritis, headache, nausea, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the antibacterial properties of the nanocomposites were tested against Escherichia coli, and it was found that Ag-containing compounds originating from the Na-modified zeolite demonstrated the highest activity. Kraljević Pavelić et al, , 2017Aparicio-Vázquez et al 2 21;Hao et al 2021;Tsiouris et al 2021;Servatan et al 2020;Abd-Elsatar et al 2019;Eroglu et al 2019;Krajišnik et al 2019;Mastinu et al 2019;Behnoosh Hossein et al 2018;Nizet al 2018;Milenkovic et al, 2017;Cutovic, 2017;Giordani et al 2019Giordani et al , 2017Li et al, 2016;Rieger et al 2016;Katsoulos et al 2016;Prasai et al 2016;Sabbioni et al 2016;Tomečková et al 2016;Toledano et al, 2015;Beltcheva et al 2015;Federico et al 2015;Gandy et al 2015;Lamprecht et al 2015;Laurino et Palmiri, 2015;Saracci, 2015;Ortega-Guerrero et al 2015Potgieter et al 2014;Aiurofiq, 2014;Selvam et al 2014;Basha et al 2013;Montinaro et al 2013;Wu, Q.J. et al 2013;Wu, Y. et al 2013;Saint-Cricq et al 2012;Hrenovic et al 2012aHrenovic et al , 2012b…”
Section: Application Of Zns In Agriculturementioning
confidence: 99%